Inspirational leadership and its impact on organizational health reinforcement at technical colleges for girls (The International Journal of Educational Sciences and Arts, 2024)
Study Objectives: Reveal the degree of practicing Inspirational leadership at technical colleges according to its dimensions, reveal level of applying organizational health in technical colleges according to its dimensions, and identify the nature of statistically significant correlation among means of practicing inspirational leadership and the level of organizational health at technical colleges from training staff viewpoints and those responsible for administrative work. Additionally, find the statistically significant differences in the responses of study respondents towards inspirational leadership practices that attributed to variables of (Academic Degree-major-years of experience – job description).Study Methodology: The study adopted the correlational descriptive approach, and the questionnaire as tool applied to a sample consisting of (60) members of study community, of training staff and those responsible for administrative work.Study Results: The study conducted the following results:-   The degree of practicing inspirational leadership at Technical College according to its dimensions was high.-   The level of organizational health at Technical College according to its dimensions was high.-   There is a direct positive relationship between practicing inspirational leadership and reinforcement of organizational health at technical colleges. -   There are statistically significant differences at level of (0.05) or less between responses of study respondents towards inspirational leadership practices on the two dimensions of self-confidence and empowering others, attributed to academic degree, in favor of those with bachelor's degree.-   There are no statistically significant differences at level (0.05) or less in the responses of the study respondents regarding the level of organizational health in all its dimensions.Study Recommendations: In light of the results, the study recommended several recommendations include: -   Strengthening and developing managers' knowledge of inspirational leadership and its applications in the field of educational practice through training programs.-   Enhancing and developing the knowledge of managers in the field of educational leadership through transferring the mechanism of its application to other educational institutions and documenting it through training programs.
Keywords: Inspirational Leadership; Organizational Health; Technical Colleges